2009
DOI: 10.1007/s11002-009-9092-3
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of pharmaceutical marketing

Abstract: Successful innovation of prescription drugs requires a substantial amount of marketing support. There is, however, much concern about the effects of marketing expenditures on the demand of pharmaceutical products (Manchanda et al., Market Lett 16(3/4):293-308, 2005). For example, excessive marketing could stimulate demand for products in the absence of a fundamental need. It also has been suggested that increased marketing expenditures may reduce the price elasticity of demand and allow firms to charge higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
2
28
0
1
Order By: Relevance
“…Investigating the Dutch pharmaceutical market, Leeflang and Wieringa concluded that in case of most drugs, the price of the drug has no effect on demand and doctors' decisions. Their results were supported by the study of Gönül et al in 2010(Leeflang -Wieringa, 2010. Consequently the authors declare that only clinical considerations should be present during drug prescription, both by doctors and patients.…”
Section: Supply Sidementioning
confidence: 63%
See 2 more Smart Citations
“…Investigating the Dutch pharmaceutical market, Leeflang and Wieringa concluded that in case of most drugs, the price of the drug has no effect on demand and doctors' decisions. Their results were supported by the study of Gönül et al in 2010(Leeflang -Wieringa, 2010. Consequently the authors declare that only clinical considerations should be present during drug prescription, both by doctors and patients.…”
Section: Supply Sidementioning
confidence: 63%
“…This leads to higher prices, which finally emerges as a loss of the society (Windmeijer et al, 2005). In contrast with Windmeijer et al, Leeflang and Wieringa state that this effect is not significant (Leeflang -Wieringa, 2010). About their work, it is important to mention that it has investigated the quasi totally funded Dutch pharmaceutical market.…”
Section: The Role Of Price In Decision Making On Drug Prescriptionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a number of studies category demand data are pooled over categories. Leefl ang and Wieringa ( 2010 ) demonstrate that pooling across categories should be avoided as such studies (e.g., Iizuka and Jin 2005 ) are more likely to generate biased results than those studies which do not.…”
Section: Product Category Level Demand Effects Of Pharmaceutical Prommentioning
confidence: 96%
“…However, clinicians are not so easily misled. In reality, marketing has only a modest effect on demand for pharmaceutical products [22]. A more plausible (and simple) explanation is that clinicians (and patients) use ICS-based therapy for COPD because they work.…”
mentioning
confidence: 99%